Effects of Intra-Uterine Fluid Accumulation after Artificial Insemination on Luteal Function in Mares - Francesca Freccero; Beatrice Mislei; Diego Bucci; Francesco Dondi; Gaetano Mari (Animals, 2022)
After breeding or artificial insemination, especially with frozen/thawed semen, mares often develop a persistent uterine inflammation, which is diagnosed by intra-uterine fluid accumulation. Here, we explored whether intra-uterine fluid accumulation affects corpus luteum function and tested the hypothesis that intra-uterine fluid accumulation after artificial insemination alters blood flow in the corpus luteum and plasma progesterone concentrations. A total of 40 Standardbred mares were artificially inseminated with frozen-thawed semen 30 to 36 h after induction of ovulation, and cases with or without intra-uterine fluid accumulation were detected by ultrasound 12 h after insemination. Luteal blood flow was measured by Power Doppler ultrasonography 3 and 6 days after ovulation, progesterone concentration was measured in peripheral plasma by ELISA 6 days after ovulation, and pregnancy was diagnosed by ultrasonography 14 days after ovulation. Luteal blood flow increased between 3 and 6 days after ovulation, but blood flow did not differ significantly between cases with (n = 28) and without (n = 25) intra-uterine fluid accumulation after insemination. Surprisingly, progesterone concentrations were higher in cases of intra-uterine fluid accumulation than cases without (9.3 ± 1.1 vs. 6.6 ± 0.5 ng/mL, p = 0.048). Pregnancy was less likely in cases with intra-uterine fluid accumulation than in cases without (10/28 vs. 17/25, p = 0.019), and there was a negative correlation between the severity of intra-uterine fluid accumulation and per cycle pregnancy rate. These data suggest that although intra-uterine fluid accumulation increases the secretion of progesterone, pregnancy is more dependent on uterine health than ovarian function.